The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1182/bloodadvances.2020001827
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of salivary microbiota injury and oral mucositis in recipients of allogeneic hematopoietic stem cell transplantation

Abstract: Abstract Oral mucositis (OM) is a common debilitating dose-limiting toxicity of cancer treatment, including hematopoietic stem cell transplantation (HSCT). We hypothesized that the oral microbiome is disturbed during allogeneic HSCT, partially accounting for the variability in OM severity. Using 16S ribosomal RNA gene sequence analysis, metabolomic profiling, and computational methods, we characterized the behavior of the salivary microbiome and metabolome of 184… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(87 citation statements)
references
References 28 publications
1
81
2
Order By: Relevance
“…Our results suggest that comparing the absolute feature frequencies (or relative frequencies) in different experiments leads to lower accuracy than measuring the fold change, as expressed by differences in the logged frequencies. Indeed, in most of our recent results [14, 16, 21, 32], we found that such a log normalization is essential.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Our results suggest that comparing the absolute feature frequencies (or relative frequencies) in different experiments leads to lower accuracy than measuring the fold change, as expressed by differences in the logged frequencies. Indeed, in most of our recent results [14, 16, 21, 32], we found that such a log normalization is essential.…”
Section: Discussionmentioning
confidence: 72%
“…4 Do not perform other dimension reductions. results [14,16,21,32], we found that such a log normalization is essential.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Many AML patients will go on to develop oral or dental complications from their cancer treatment, and the composition of the oral microbiome plays a role in determining this risk. In particular, the oral microbial composition has been shown to be associated with the development of oral mucositis, which is characterized by ulcerative lesions in the mouth, in hematopoietic stem cell transplantation patients with hematologic malignancies [ 37 , 38 ]. Microbiome risk factors have also been associated with the development of oral candidiasis, which is an infection of the oral cavity, during cancer chemotherapy [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Shouval et al demonstrated that also oral microbiome-derived metabolites are altered in patients developing oral mucositis during HSCT. They analyzed the salivary metabolic profile of patients with and without severe oral mucositis, showing a reduction in N-acetylputrescine and agmatine, metabolites involved in the polyamine pathway [ 30 ]. Polyamines are small polycationic molecules produced by commensal bacteria with a wide array of biological functions including preservation of mucosal barrier integrity [ 77 ].…”
Section: Polyamines and Breath Metabolitesmentioning
confidence: 99%